2011
DOI: 10.1021/jp2020947
|View full text |Cite
|
Sign up to set email alerts
|

Ring Currents in Polycyclic Sodium Clusters

Abstract: In the recent work by Khatua et al. [Khatua, S.; Roy, D. R.; Bultinck, P.; Bhattacharjee, M.; Chattaraj, P. K. Phys. Chem. Chem. Phys. 2008, 10, 2461-2474 the synthesis and structure of a fac-trioxo molybdenum metalloligand and its sodium complex containing 1D hexagonal chains of sodium ions was reported. In the same paper, the aromaticity of hexagonal Na-clusters was quantified by means of the nucleus-independent chemical shift and electronic multicentre indices. It was shown that the aromaticity of hexagonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
(121 reference statements)
1
15
0
Order By: Relevance
“…It has been shown that by using basis sets with an effective core potential, one is able to reduce the impact of the core electrons thereby allowing a more efficient analysis of global current densities in Na-clusters. 76 In addition, NICS values calculated using an effective core potential are in good agreement with all electron NICS values. 76 In all calculations a unit magnetic field perpendicular to the molecular plane was used and the calculated ring currents were plotted on a grid in a set of planes parallel to the molecular plane with a diatropic current represented by a counterclockwise circulation.…”
Section: Theoretical Studysupporting
confidence: 59%
“…It has been shown that by using basis sets with an effective core potential, one is able to reduce the impact of the core electrons thereby allowing a more efficient analysis of global current densities in Na-clusters. 76 In addition, NICS values calculated using an effective core potential are in good agreement with all electron NICS values. 76 In all calculations a unit magnetic field perpendicular to the molecular plane was used and the calculated ring currents were plotted on a grid in a set of planes parallel to the molecular plane with a diatropic current represented by a counterclockwise circulation.…”
Section: Theoretical Studysupporting
confidence: 59%
“…This index became popular rapidly because of its easy computation in practically all quantum chemical packages. However, its indiscriminate use has often been criticized . These criticisms have pointed out to the validity of NICS being limited by spurious contributions from the in‐plane tensor components, which are not related with the aromaticity phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…However, its indiscriminate use has often been criticized. [18][19][20][21][22][23][24][25][26] These criticisms have pointed out to the validity of NICS being limited by spurious contributions from the in-plane tensor components, which are not related with the aromaticity phenomenon. To avoid these issues, different ways to analyze NICS have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…A growing community of researchers is involved in the computation and visualization of ring currents . Yet, at odds with what happened long ago with the chemical shift scale, international committees have not suggested any convention either for their graphical representation or for their quantitative measures, and therefore, care is always needed when looking or comparing maps or tables to understand the connection between direction of arrows, numerical values and tropicities.…”
Section: The Magnetic Perspective On the Annulene‐within‐an‐annulene mentioning
confidence: 99%